Revision of the genus Amazunculus Rafael (Diptera: Pipunculidae), with description of six new species - Marques, Dayse W.a.; Skevington, Jeffrey H.; Rafael, José A. (Zootaxa, 2019)
The species of the genus Amazunculus Rafael (Diptera: Pipunculidae) are large bodied flies, easily identified by their flattened hind tarsus and curved dm-m wing vein. The species of this Neotropical genus are revised, including six new species: Amazunculus acreanus sp. nov. (type-locality: Brazil, Acre, Rio Branco), A. bethoi sp. nov. (type-locality: Brazil, Amazonas, Carauari), A. francyae sp. nov. (type-locality: Ecuador, Napo), A. manauara sp. nov. (type-locality: Brazil, Amazonas, Manaus), A. panamensis sp. nov. (type-locality: Panama, Canal Zone) and A. psilalarius sp. nov. (type-locality: Venezuela, Amazonas). All these new species are described with an emphasis on structures of the male terminalia, which are fully illustrated. An identification key to the twelve species of Amazunculus is provided. The first record of Amazunculus in Central America (Panama) is documented.